2015
DOI: 10.1111/epi.13084
|View full text |Cite
|
Sign up to set email alerts
|

The direct cost of epilepsy in the United States: A systematic review of estimates

Abstract: SUMMARYObjective: To develop estimates of the direct cost of epilepsy in the United States for the general epilepsy population and sub-populations by systematically comparing similarities and differences in types of estimates and estimation methods from recently published studies. Methods: Papers published since 1995 were identified by systematic literature search. Information on types of estimates, study designs, data sources, types of epilepsy, and estimation methods was extracted from each study. Annual per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
144
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(151 citation statements)
references
References 39 publications
5
144
0
2
Order By: Relevance
“…It would be important to learn more about the factors that contribute to this high level of variability. Of course, and as mentioned, one factor is most likely to be the severity of epilepsy, as reflected by the number and severity of seizures [37,38]. But there may be other factors as well, such as the financial resources of the parents, the age (stage of DS) of the child, responsiveness of seizures to therapies, severity of comorbidities, and availability of social support and extent of the social support network of the family.…”
Section: Direct Costs Of Dsmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be important to learn more about the factors that contribute to this high level of variability. Of course, and as mentioned, one factor is most likely to be the severity of epilepsy, as reflected by the number and severity of seizures [37,38]. But there may be other factors as well, such as the financial resources of the parents, the age (stage of DS) of the child, responsiveness of seizures to therapies, severity of comorbidities, and availability of social support and extent of the social support network of the family.…”
Section: Direct Costs Of Dsmentioning
confidence: 99%
“…However, we do not know if the findings from that study from a single clinic generalize to the families of children with DS in other parts of Germany or to clinics in other countries with different medical systems. One recent systematic review of the direct costs of epilepsy in general (including children and adults) in the US found direct epilepsy costs to range from $1022 to $19,749 [about €950 to €18,500] over a one-year period [37]. Another study of the direct and indirect costs of epilepsy in general in Germany found the mean direct costs to be €1619 in a 3-month period (€6476 over 12 months) and the 3-month maternal and paternal indirect costs to be €1231 and €83 in 2011 amounts [estimated annual indirect costs €4924 and €332], respectively [38].…”
Section: Direct Costs Of Dsmentioning
confidence: 99%
“…The precise mechanisms that contribute to pharmacoresistance remain unclear and the subject of scientific investigation . Pharmacoresistant epilepsy contributes to greater economic burden, more severe comorbidities, and increased risk of sudden unexpected death in epilepsy (SUDEP) . Despite continuous advancements in our understanding of the underlying disease biology and a myriad of new ASDs, the percentage of patients with epilepsy who do not achieve seizure freedom with available medications remains unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its chronicity and unpredictability, it confers a significant burden to its bearers, their loved ones, and the society as a whole 2 3. An examination of recent studies based on claims data from large general populations in the USA identified epilepsy-specific annual cost estimates ranging from $8412 to $11 354 per person 4. It is for such reasons that a recent report from the Institute of Medicine urged for actions to improve the lives of people with epilepsy and their families 5…”
Section: Introductionmentioning
confidence: 99%